COMMUNITY PARTICIPATION IN THE DEVELOPMENT OF SIPURIO VILLAGE-OWNED BUSINESS AGENCY (BUMDES) IN LALABATA VILLAGE, KECAMATAN TANETE RILAU KABUPATEN BARRU - Masyitah; Hesti Lestari (Meraja journal, 2022)
Copyright (c) 2022 Meraja journal